2021
DOI: 10.1002/app.51734
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of gum rosins for their use as sustainable additives in polymeric matrices

Abstract: There is a growing interest in the use of non‐polluting compounds, which come from renewable sources, and which performance in their scope is equivalent to their synthetic similes. In this work, five types of rosins from different sources were studied, verifying the existence of differences that can be inferred in their subsequent use and application as material additives. For the study, rosins were analyzed using gas‐mass chromatographic techniques, infrared spectrophotometry (FTIR), differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Oxidation is a process that can occur during the manufacture of polyolefins and can affect the quality and properties of polyolefins. Polymers can be sensitive to oxidation due to the presence of double bonds or carbonyl groups, which are vulnerable points to oxidation [29,30,55,56]. Due to its extremely low density, polypropylene (PP) is a polymer of petrochemical origin that is widely used in many sectors because it can be heated, cooled, and reheated without losing its composition.…”
Section: Multistandard Repeatability Analysis Of Cyanox 1790 In Ch2cl...mentioning
confidence: 99%
“…Oxidation is a process that can occur during the manufacture of polyolefins and can affect the quality and properties of polyolefins. Polymers can be sensitive to oxidation due to the presence of double bonds or carbonyl groups, which are vulnerable points to oxidation [29,30,55,56]. Due to its extremely low density, polypropylene (PP) is a polymer of petrochemical origin that is widely used in many sectors because it can be heated, cooled, and reheated without losing its composition.…”
Section: Multistandard Repeatability Analysis Of Cyanox 1790 In Ch2cl...mentioning
confidence: 99%
“…The choice of this model was based on previous calculations that suggested that the coordination of TiCl 4 to the (104) plane is weak or even unstable. In comparison, the coordination of TiCl 4 to the (110) plane is energetically favorable [14]. a suitable acceptor of electrons and is willing to accept electrons from other atoms or molecules.…”
Section: Adsorption Energiesmentioning
confidence: 99%
“…TGA was performed on a Perkin Elmer TGA7 thermogravimetric analyzer at a heating rate of 20 • C min − 1 with a scan range from room temperature to 600 • C. In each test, a 10 mg sample was examined under N 2 with a flowing rate of 60 mL min − 1 [52]. With the TG and DTG curves, all the thermal degradation data was obtained [59,60].…”
Section: Thermogravimetric Analyzer (Tga)mentioning
confidence: 99%